Purchase Decision for Halal Network International (HNI) Products - Yanti, Meri; Bayu Winanda, Aldy; Wira Gusti Pangestu, Yoga (Golden Ratio of Data in Summary, 2024)
Indonesia is the world's largest Muslim majority. With so many Muslim consumers, halal labeling is essential for every product promoted. Halal-labeled products include food and beverages, as well as other consumer goods such as skincare, medications, and other products. Besides from that, price influences consumers' decisions to purchase halal products for daily use. This research aims to examine that halal labelling and price influences purchasing decisions for HNI (Halal Network International) products in Dumai City. The respondents in this study were 100 people selected using the Proportionate Stratified Random Sampling approach. This study employs a quantitative technique, utilising a Likert measurement scale. Data is collected using questionnaires, which are then processed with the Statistical Product and Services Solution (SPSS). The study's findings show that halal labels have a positive and significant influence on purchase decisions, as do pricing. Furthermore, there is a positive and significant between the halal label and the price, which both influence purchase decisions.